India's efforts towards improving maternal healthcare: a narrative review of government maternal health schemes - Raksha Yadav; Latha Venkatesan; Rajlaxmi Mundhra; Hemlata (International Journal Of Community Medicine And Public Health, 2026)
Maternal mortality is still a major public health concern. India stands second across the globe in absolute maternal deaths. Even though the country has reduced the maternal mortality ratio (MMR) from 570 in 1990 to 97 per 100,000 live births in 2020. The present narrative review traces the evolution of centrally sponsored Government of India maternal health schemes from 1952 to 2019, and examines their objectives, key interventions and outcomes against the national targets and sustainable development goal (SDG) 3. Literature was identified from PubMed/MEDLINE, Scopus, google scholar and the Cochrane library and supplemented by government policy documents, NFHS data and WHO/UNICEF reports and synthesized narratively in chronological order. From the family planning programme (1952) to the launch of SUMAN scheme in 2019, several schemes have strengthened the maternal health continuum of care in India. JSY and JSSK have significantly increased institutional delivery (41% in 2005 to 88.6%, NFHS-5) and reduced out of pocket expenditure. Continued persistence of socioeconomic inequities, disparities and urban–rural gaps limit universal coverage of maternal health schemes in India. India’s estimated 2023 MMR of 116 which means it is off track to meet the SDG 3.1 target of below 70 by 2030. India’s maternal health policy architecture is characterised by sustained government commitment. but equity-focused implementation, demand-side interventions and evidence-based programme refinement are crucial to achieving zero preventable maternal deaths.